Volatile compound profile of rice bran extract: Gas chromatography-mass spectrometry optimization and the impact of processing and storage - Le Hoang Phuong; Nguyen Van Thanh; Ly-Nguyen Binh (Journal of Agriculture and Food Research)
This study optimized gas chromatography-mass spectrometry analysis of rice bran extract to maximize volatile compound detection. Optimal conditions, determined using response surface methodology, included a temperature program (40 °C, 1 min hold; 10 °C/min ramp to 160 °C, 3 min hold; 20 °C/min ramp to 300 °C, 10 min hold) and static headspace sampling (50 °C, 30 min equilibration, 20 % saturated NaCl solution). Sterilization significantly altered the volatile profile, reducing compound diversity and impacting overall aroma. Subsequent storage at room temperature over three months resulted in further changes, with increases in some compounds (e.g., cyclopentane) and decreases in others (e.g., dl-2-ethylhexyl chloroformate, associated with pungent off-flavors). Principal component analysis clearly distinguished volatile profiles based on storage duration. These findings provide critical insights for optimizing rice bran processing and developing high-value-added products by enhancing analytical techniques and understanding the effects of processing and storage on volatile flavor compounds, ultimately contributing to the improved utilization of this valuable agricultural byproduct.